Yarrowia lipolytica Adhesion and Immobilization onto Residual Plastics - Botelho, Alanna; Penha, Adrian; Fraga, Jully; Barros-Timmons, Ana; Coelho, Maria Alice; Lehocky, Marian; Štěpánková, Kateřina; Amaral, Priscilla (Polymers, 2020)
Research in cell adhesion has important implications in various areas, such as food processing, medicine, environmental engineering, biotechnological processes. Cell surface characterization and immobilization of microorganisms on solid surfaces can be performed by promoting cell adhesion, in a relatively simple, inexpensive, and quick manner. The adhesion of Yarrowia lipolytica IMUFRJ 50682 to different surfaces, especially potential residual plastics (polystyrene, poly(ethylene terephthalate), and poly(tetrafluoroethylene)), and its use as an immobilized biocatalyst were tested. Y. lipolytica IMUFRJ 50682 presented high adhesion to different surfaces such as poly(tetrafluoroethylene) (Teflon), polystyrene, and glass, independent of pH, and low adhesion to poly(ethylene terephthalate) (PET). The adhesion of the cells to polystyrene was probably due to hydrophobic interactions involving proteins or protein complexes. The adhesion of the cells to Teflon might be the result not only of hydrophobic interactions but also of acid-basic forces. Additionally, the present work shows that Y. lipolytica cell extracts previously treated by ultrasound waves (cell debris) maintained their enzymatic activity (lipase) and could be attached to polystyrene and PET and used successfully as immobilized biocatalysts in hydrolysis reactions.
Keywords: polymer surfaces; recycling; immobilization; Yarrowia lipolytica; adhesion